Love me, love me not. Vol. 4 - Sakisaka, Io; Thistlethwaite, Nancy (Shojo beat manga., 2020)
"Fast friends Yuna and Akari are complete opposites--Yuna is an idealist, while Akari is a realist. When lady-killer Rio and the oblivious Kazuomi join their ranks, love and friendship become quite complicated!... Love and friendship have become quite complicated for these four friends. Rio's kiss is the result of being unable to rein in his feelings after he discovers Akari, who is working to keep the family together, and Yuna, who loves Rio, are shocked. Can Yuna help Rio understand what's at stake?"--Provided by publisher.